Comparative Case–Control analysis of a dedicated self‐expanding Biolimus A9‐eluting Bifurcation stent versus provisional or mandatory side branch intervention strategies in the treatment of coronary bifurcation lesions. Issue 1 (21st September 2016) - Ohlow, Marc‐Alexander; Farah, Ahmed; Richter, Stefan; El‐Garhy, Mohamad; von Korn, Hubertus; Lauer, Bernward
Abstract : Background: In a number of coronary bifurcation lesions, both the main vessel and the side branch (SB) need stent coverage. Objectives: To analyze the procedural performance and the impact on radiation times (RT) and contrast medium consumption (CMC) of the Axxess™ stent system (Biosensors, Switzerland) treating de novo bifurcation lesions (DBL). Methods: One hundred and ten consecutive prospectively enrolled cases (Axxess Group) and 110 age, sex, and lesion location matched controls undergoing mandatory (Group A, n = 56) or provisional (Group B, n = 54) SB intervention were analyzed. Results: Although more pre‐dilatation was performed in the Axxess Group (92.7% vs. 46.4% [Group A] vs. 24.1% [Group B]), and more stents were used (2.4 vs. 1.2 vs. 1.05), RT and CMC were significantly lower in the Axxess Group [7.9 min/129 ml vs. 14.2 min/209 ml vs. 7.8 min/152 ml; P < 0.001]. Final Thrombolysis In Myocardial Infarction three flow in both branches was significantly more frequent in the Axxess Group (98.2% vs. 94.6% vs. 88.9%; P = 0.02), and post‐interventional troponin T elevations were the lowest in the Axxess Group. Eighty one percent of the Axxess‐stents could be implanted without technical difficulties. Difficult implantations procedures were mainly related to coronary anatomy. There was no safety concerns (cardiac death, stent‐thrombosis) compared to controls. Cumulative 6‐months MACE rates were 11% versus 23% versus 25%. TLR rates at 6‐months were 5%, 18%, and 15%, respectively. Conclusions: Axxess bifurcation stent system procedures were associated with significantly less RT and CMC compared to conventional DBL therapy strategies. Difficult coronary anatomy may hinder successful implantation and a learning curve has to be considered. © 2016 Wiley Periodicals, Inc.